2021
DOI: 10.3390/biology10090925
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of New Aggressive Leaf Rust Races with the Potential to Supplant the Resistance of Wheat Cultivars

Abstract: Characterization of the genetic structure and the physiological races of Puccinia triticina is a growing necessity to apply host genetic resistance against wheat leaf rust as a successful control strategy. Herein, we collected and identified about 130 isolates of P. triticina from 16 Egyptian commercial wheat cultivars grown at different locations, over two seasons (2019/2020 and 2020/2021). The 130 isolates of P. triticina were segregated into 17 different physiological races. TTTST and TTTKS were the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…This can also be achieved by developing rust resistant genotypes or by successful varietal manipulation of the available genotypes throughout the country to avoid heavy infection to the susceptible genotypes [ 1 ]. The emergence of new races capable of breaking the resistance in the new varieties, such as the emergence of the TTTST race on Shandweel-1, Sakha-94 and Sakha-95 varieties was reported [ 5 ]. Therefore, the second line of control methods should be used, which is chemical fungicides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can also be achieved by developing rust resistant genotypes or by successful varietal manipulation of the available genotypes throughout the country to avoid heavy infection to the susceptible genotypes [ 1 ]. The emergence of new races capable of breaking the resistance in the new varieties, such as the emergence of the TTTST race on Shandweel-1, Sakha-94 and Sakha-95 varieties was reported [ 5 ]. Therefore, the second line of control methods should be used, which is chemical fungicides.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the cultivation of more than one resistant variety was utilized [ 1 ]. The emergence of new disease races and the breaking of resistance in the varieties increase disease losses [ 5 ]. Therefore, the second line of disease control is to rely on chemical control.…”
Section: Introductionmentioning
confidence: 99%
“…The main defect in this type of resistance is that, due to the race adaptation ability, the disease could overcome the resistant genes and produce new virulent races that cause epidemics situation in single gene wheat cultivars (Folr, 1956;Flor, 1971). This is the recent situation in the Egyptian fields where different Pt races among the Egyptian governorates and growing seasons have been reported that resulted in a breakdown of the resistance in some important Egyptian cultivars (Omara et al, 2021). To date, more than 80 leaf rust resistance genes (Lr) have been identified and formally cataloged in wheat, most of them confer race specific resistance (McIntosh et al, 1995(McIntosh et al, , 2008(McIntosh et al, , 2013Gill et al, 2019;Bhavani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The difference in the genetic background of resistance reflects the difference between the type of infection and the disease. This is due to the appearance of new virulent race in pathogen populations therefore, the type of infection of some varieties may change over time (Omara et al, 2021). Some varieties can maintain resistance for many years but become susceptible after a period of time (Al-Maaroof, 1997).…”
Section: Discussionmentioning
confidence: 99%